Effect of Variety and Spraying of Humic Acid on Growth and Produc-tivity of Silk Corn (Zea mays L.) and it‘s content of some active com-pounds to the date of harvesting - S. Abaka, Ahmad J.; S. Al-Asady, Maher H. (Journal of Kerbala for Agricultural Sciences, 2017)
A field experiment was carried out during the autumn season 2016 in the Nile area, located 8 km north-east of Hilla city to study the effect of the varity and spraying of the humic acid in the growth and productivity of silk corn and its content of some effective compounds of corn Zea mays L. to the date of harvesting, Randomized Complete Block Design (RCBD) Factorial Experiment with three replicates The first two synthetic varieties of corn are Fajr1, EL-Maha and Baghdad3, and the second agent is sprayed with concentrations of 0, 0.5, 1.0 and 2.0gm.L-1. To harvest the calf 14 to 28 days after the break Top of the Aer. according, the results showed that the superiority of Fajr 1 by giving the highest average number of leaves and the content of total chlorophyll and soft and dry weight of the silk corn, reaching 16.95 leavs.Plants-1 and SPAD 51.61 and the weight of soft and dry of the silk corn 8.81 and 2.86 gm.Aer-1 for cutting after 14 days 4.71 and 3.25 for gm.Aer-1 Picking after 28 days sequentially, and the superiority of variety EL-Maha in giving the highest in the phenols content of Flavonoids and carotenoids total of cutting after 14 days amounted to 155.16 and 48.40 and 10.75 mg.Kg-1 dry weight while variety Fajr1 in silk corn content of the compounds above to harvest after 28 days 95.64 and 47.65 and reached 6.03 mg.Kg-1 dry weight sequentially, and gave the concentration of spray 2.0 gm.L-1 higher averages of the recipes above amounted to 16.93 leavs.Plants-1 and SPAD 53.61 reached mild and dry weight of silk corn 9.66 and 2.94 gm.Aer-1 for cutting after 14 days and 5.76 and 3.70 gm.Aer-1 for cutting after 28 days sequentially, and the superiority of the concentration of spray 2.0 gm.L-1 to give the highest averages in the suggested phenols total and Flavonoids of cutting after 14 days amounted to 140.59 and 53.29 mg.Kg-1 dry weight while the concentration of the highest averages in the same content Alanthusianinat carotenoids total date cut after 28 days amounted to 7.86 and 6.32 mg.Kg-1 dry weight sequentially